Reversible airway obstruction in cystic fibrosis. Issue 10 (October 1980) - Ormerod, L P; Thomson, R A; Anderson, C M; Stableforth, D E
Abstract : Fourteen (29%) of 48 children with cystic fibrosis had a greater than 15% improvement in forced expiratory volume in one second, or in forced vital capacity after inhalation of salbutamol. All these children were atopic (one or more positive prick tests) and had a significantly higher mean serum IgE than either non-atopic subjects or those atopic subjects without airways reversibility (p less than 0.02). Half of those with airways reversibility had or subsequently developed the clinical picture of allergic bronchopulmonary aspergillosis. Of the whole group 81% were atopic, of whom 77% had a positive reaction to A fumigatus, 64% to housedust, and 56% each to grass pollen and cat hair. Children who were not atopic had significantly better spirometry (p greater than 0.05) than those who were. Children with skin hypersensitivity to A fumigatus had identical spirometry to those who were atopic without reactivity to A fumigatus. Serum precipitins to A fumigatus were present in 48%. Serum precipitins to pancreatin were present in 71%, but the presence of these precipitins did not correlate with atopy, airways reversibility, or serum IgE.